Assessment of trends and factors influencing the diversification of activities in the construction sector - BOSHTAN , Anatoliy (Ways to Improve Construction Efficiency, 2025)
In today’s context of economic instability and global transformations, the construction industry faces the need for a profound restructuring of its development strategies. One of the key tools for ensuring the resilience and competitiveness of enterprises is the diversification of activities, which not only minimizes risks but also creates new growth vectors. This study focuses on assessing the trends and factors influencing the diversification process in the construction sector, as well as determining the role of digital technologies and the regulatory environment in this transformation. The article systematizes the main directions of diversification – horizontal, vertical, functional, and regional – and analyzes their interaction with both external and internal determinants. It examines the influence of public policy, institutional frameworks, technological innovation, and the level of digital maturity of enterprises on the intensity of diversification processes. It has been established that modern companies are shifting from narrowly specialized business models to multifunctional structures capable of operating simultaneously in construction, asset management, energy efficiency, and digital services. Particular attention is paid to the impact of digital transformation, especially the implementation of BIM, IoT, AI, ERP, and PMIS systems, which act as catalysts for functional diversification. The study proposes analytical formulas for measuring the level of institutional attractiveness, digital penetration, and adaptive elasticity of enterprises, allowing for a quantitative assessment of their diversification potential. It has been revealed that sustainable diversification is possible only when a balance is achieved between internal resources (financial, human, digital) and external challenges (economic, regulatory, technological). The findings indicate that diversification has evolved from a defensive response to an active strategic mechanism for development, where flexibility, analytics, and digital integration serve as key factors of long-term efficiency. The concept proposed in the article allows diversification to be viewed not merely as a reaction to external challenges but as a proactive tool for shaping the future of construction companies within the digital economy.